(untitled) (Research, Society and Development, 2023)
Studies have demonstrated that certain compartments of SOM are capable of detecting transformations in soil C contents with management, that is, with or without burning, but are able to detect, more quickly, observed reductions are generally greater than the observed, thus considering the total C content of the soil. The study was carried out in the eastern Amazon, Northeast of Pará, in Igarapé-Açu, yellow Latosol soil, in experimental areas of the communities of Cumaru, Nova Olinda (in properties of small rural producers) and UFRA-FEIGA. The use systems consist of 06 (six) treatments, which are: T1 CC (Cumaru Capoeira), T2 CSQT (Cumaru without comminuted burning), T3 CQ (Cumaru burning), T4 UFC (UFRA Capoeira), T5 UFSQT burned), T6UFQ (UFRA burning). As well as, some SAFs. Soils were sampled at depths of 0-5 cm, 5-10 cm and 10-20 cm. The densitometric fractions were separated for the determination of carbon contents by combustion in the LECO CHN-S TRUSTEC elemental analyzer. The variables were submitted to analysis of variance, compared with the SNK test with the SISVAR statistical program. The fraction that stored carbon was the free light in the systems where there was no burning, with its sensitivity of the soil management system, where there was a greater stirring of this fraction if it was less present. The light, free fraction concentrated by storing more carbon than the occluded fraction in function of its different mechanisms and chemical composition.